2006
DOI: 10.1016/j.ijpara.2005.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a putative aquaporin from Encephalitozoon cuniculi, a microsporidia pathogenic to humans

Abstract: The microsporidia are a group of obligate intracellular parasitic protists that have been implicated as both human and veterinary pathogens. The infectious process of these organisms is believed to be dependent upon the rapid influx of water into spores, presumably via aquaporins (AQPs), transmembrane channels that facilitate osmosis. An AQP-like sequence of the microsporidium Encephalitozoon cuniculi (EcAQP), when cloned and expressed in oocytes of Xenopus laevis, rendered these oocytes highly permeable to wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Phylogenetic relationships were estimated using ClustalW (Thompson et al 1994) followed by applying a Bayesian approach based on Markov chain Monte Carlo (MCMC) implemented in the computer program MrBayes 2.09 (Ronquist and Huelsenbeck 2003). Shown are the phylogenetic fungal classification (down to orders), the mean number and standard deviations (in brackets) of orthodox aquaporins (OP), X-intrinsic proteins (XIPs), and aquaglyceroporins (AGP) (Ghosh et al 2006), NPA/NPG) into consideration, for which water channel activity has been shown, the NPA definition needs to be further extended. In plant and animal orthodox AQPs, such modulation of the NPA motifs frequently introduces solute transfer capability of the respective AQPs in addition to water (Beitz et al 2006;Ishibashi 2006).…”
Section: Orthodox Aqpsmentioning
confidence: 99%
“…Phylogenetic relationships were estimated using ClustalW (Thompson et al 1994) followed by applying a Bayesian approach based on Markov chain Monte Carlo (MCMC) implemented in the computer program MrBayes 2.09 (Ronquist and Huelsenbeck 2003). Shown are the phylogenetic fungal classification (down to orders), the mean number and standard deviations (in brackets) of orthodox aquaporins (OP), X-intrinsic proteins (XIPs), and aquaglyceroporins (AGP) (Ghosh et al 2006), NPA/NPG) into consideration, for which water channel activity has been shown, the NPA definition needs to be further extended. In plant and animal orthodox AQPs, such modulation of the NPA motifs frequently introduces solute transfer capability of the respective AQPs in addition to water (Beitz et al 2006;Ishibashi 2006).…”
Section: Orthodox Aqpsmentioning
confidence: 99%
“…Most studies have shown that some biological changes during germination are associated with AQP [24,25], SWP [29][30][31], polar tube protein [30,39,40], protease [26][27][28], carbohydrate conversion [33,34,41], and so on. Biological control against microsporidia depending on the mechanism of spore germination is far from successful because of the lack of knowledge on the key proteins involved in germination.…”
Section: Discussionmentioning
confidence: 99%
“…It is universally accepted that an appropriate stimulus, such as pH, ionic species, osmotic pressure, temperature, and radiation [21][22][23], can make spores germinate, however the mechanism have not been fully elucidated. An increase in the intrasporal osmotic pressure can make spores germinate, and the change in the intracellular osmotic pressure has been proven to be associated with some proteins such as aquaporins (AQP) [24,25]. Many studies have shown that protease, such as metalloprotease and subtilisin-like protease, may play some roles in the germination and invasion processes [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This extrusion process is almost certainly dependent on the rapid influx of water into spores (Wittner and Weiss 1999). We have previously cloned an aquaporin (AQP)‐like sequence of the microsporidium Encephalitozoon cuniculi ( Ec AQP) and in a standard functional assay for AQPs shown that Ec AQP‐transfected Xenopus laevis oocytes are significantly more permeable to water than control oocytes (Ghosh et al 2006). Here we report the production of an antiserum to recombinant Ec AQP which stains the surface of transfected X. laevis oocytes, confirming immunohistochemically our evidence for functional heterologous expression of Ec AQP in these transfected oocytes.…”
mentioning
confidence: 99%